Long-Term Results of Bilateral Lung Transplantation in Patients With End-Stage Pulmonary Lymphangioleiomyomatosis. (June 2019) - Salman, Jawad; Ius, Fabio; Sommer, Wiebke; Siemeni, Thierry; Fleissner, Felix; Alhadidi, Hani; Kugler, Christiane; Avsar, Murat; Haverich, Axel; Warnecke, Gregor; Tudorache, Igor; Kuhn, Christian
Introduction: Lymphangioleiomyomatosis (LAM) is a rare disease in women, leading to progressive deterioration of lung function and respiratory failure. We describe the outcome of patients with end-stage LAM who underwent lung transplantation at our center. Materials and Methods: The records of patients with LAM transplanted at our institution between February 1997 and May 2015 were reviewed retrospectively. Morbidity and mortality were analyzed, and actuarial survival was calculated using Kaplan-Meier methods. The cumulative survival of transplant patients with LAM at our center was compared with survival after transplantation due to different diseases at our center and the results of the International Society for Heart and Lung Transplantation. Quality of life was assessed by a patient self-report at the end of the first postoperative year. Results: During the study period, 25 patients underwent lung transplantation for LAM. All patients were women with a mean age of 50 (9) years. Thirteen patients (52%) had undergone previous thoracotomy. All patients (100%) received bilateral lung transplantation. One (4%) case of in-hospital mortality occurred and 9 (36%) late deaths. Two (8%) cases of late death were due to chronic lung allograft dysfunction. The 1-, 3-, and 5-year survival rates were 92%, 84%, and 76%, respectively. Quality-of-life ratings were above the normal in all eight 36-Item Short Form Health Survey subscales 1 year after transplantation. Conclusions: Lung transplantation offers a valuable therapy for patients with end-stage pulmonary LAM.